The response of sorghum cultivars to mixtures of compatible and incompatible isolates and different conidia concentrations of Colletotrichum sublineola. (December 2021) - Ahn, Ezekiel; Fan, Farrell; Prom, Louis K.; Odvody, Gary; Magill, Clint
Abstract: The anthracnose pathogen Colletotrichum sublineola and its sorghum host provide an excellent system to examine concepts associated with gene-for-gene resistance. In this study, an excised-leaf spot inoculation assay method was used to evaluate host-pathogen interactions across several sorghum cultivars that serve as host differentials for defining races of the pathogen. Host cultivars tested included sorghum cultivars BTx398, RTx2536, Theis and johnsongrass cultivar SH1152. The cultivars were inoculated at varying conidia concentrations both singly and in pairs with conidia from strains of C. sublineola that differ in ability to incite the disease anthracnose. The hypothesis tested was that host defense triggered by effectors produced by an avirulent strain will limit infection when simultaneously inoculated with a strain that otherwise would lead to disease. Observations revealed significant changes in disease ratings based on conidial concentrations of the C. sublineola isolates used. However, disease rating scores for combined inocula in the excised-leaf spot inoculation assays led to scores either between the scores generated by single isolates or near the score of the more virulent isolate. Highlights: Sorghum plants were co-inoculated with strains of  C. sublineola  expected to cause different disease responses. It was hypothesized that an avirulent strain will trigger host defense to limit disease by the virulent strain. Although variations were observed, the excised-leaf spot inoculation assays did not support that hypothesis. Significant changes in disease ratings were observed based on conidial concentrations of the  C. sublineola  isolates used.